Red velvet crush - Meredith, Christina (Greenwillow Books, an imprint of HarperCollinsPublishers, 2016)
"Teddy Lee's bitter rivalry with her younger sister and family dysfunction leave her ill-prepared to deal with success, but through music she gains a new perspective and begins to heal"--